Peningkatan angka kekerasan terhadap perempuan dan anak: upaya pencegahan dan perlindungan yang perlu dilakukan - Mahsunah, Nafsiyatul (Maliki Interdisciplinary Journal, 2023)
Violence against women and children is an increasing issue in Indonesia. This article discusses the prevention and protection measures that need to be taken to overcome this problem. Several preventive efforts that can be carried out are through family education, outreach to child protection and domestic violence prevention laws, as well as other preventive measures to address the causes and factors of violence. Apart from that, this article also discusses the importance of legal protection and security for victims of violence, as well as the role of government and society in tackling violence against women and children. In overcoming this problem, cooperation and support from all parties is needed to create an environment that is safe and free from violence.